Peningkatan Hasil Belajar IPAS Materi Kekayaan Budaya Indonesia melalui Penerapan PjBL pada Siswa Kelas IV SD Negeri Joho 03 Mojolaban - Prasetya, Wahid Agus; Arianti, Arin; Sularmi, Sularmi (Jurnal Ilmiah Dikdaya, 2025)
This study aims to improve the learning outcomes of fourth grade students of Joho 03 Mojolaban Elementary School on the material of Indonesian cultural richness through the application of the project-based learning (PjBL) model. This classroom action research is motivated by the low learning outcomes of students on the material. Through a learning cycle consisting of planning, action, observation, and reflection, the researcher attempts to create active, enjoyable, and meaningful learning for students. Research data were obtained through learning outcome tests and study documentation. The results of the study showed a significant increase in student learning outcomes after the application of the PjBL model. This is indicated by the increase in the average student score in each cycle. In addition, students also showed increased motivation and active involvement in the learning process. The application of the PjBL model has proven effective in improving students' understanding of Indonesian cultural richness as well as developing critical thinking, communication, and collaboration skills. Thus, the PjBL model can be used as an alternative learning model that can improve the quality of science learning in elementary schools.